2021
DOI: 10.1016/j.xkme.2021.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury and Advanced Kidney Disease in the COVID-19 Pandemic: Proceedings From a National Kidney Foundation Symposium

Abstract: The coronavirus disease 2019 (COVID-19) pandemic is an unprecedented and historic public health crisis that continues to expand and evolve. The National Kidney Foundation (NKF) held a two-part CME live virtual symposium on July 16th and July 24 th 2020 to address the multiple challenges of COVID-19 in the context of advanced chronic kidney disease (CKD). Faculty addressed the pathophysiology, impact, risks, and management of COVID-19 as it relates to advanced kidney disease. Testing, ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…We found that by December 2020, almost 700 Medicare bene ciaries who contracted COVID-19 or CLI with no pre-existing ESRD had subsequent kidney transplants, although we could not tell whether the transplants were a direct result of COVID-19. The most common pathology of COVID-19-related AKI is acute tubular injury, however, the direct effect of SARS-CoV-2 infection on renal tissue is unclear (32,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that by December 2020, almost 700 Medicare bene ciaries who contracted COVID-19 or CLI with no pre-existing ESRD had subsequent kidney transplants, although we could not tell whether the transplants were a direct result of COVID-19. The most common pathology of COVID-19-related AKI is acute tubular injury, however, the direct effect of SARS-CoV-2 infection on renal tissue is unclear (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the obstacles related to the COVID-19 pandemic, dialysis facilities were able to adjust and provide hemodialysis sessions at average monthly rates of between 2.5 and 2.8 sessions per person per week. However, patients with ESRD and with COVID-19 had remarkably high death rates, underscoring the importance of ongoing efforts to protect at-risk populations from COVID-19, especially considering concerns such as emerging SARS-CoV-2 variants, vaccine effectiveness in persons who are immunocompromised, and waning vaccine immunity over time following vaccination (32).…”
Section: Discussionmentioning
confidence: 99%
“…Other manifestations can involve other districts. Kidney damage is a frequent complication in hospitalized patients with COVID-19 with an incidence range between 10 and 80% and a significantly increased risk of intra-hospital mortality [ 70 , 71 ]. Neurological symptoms occur most commonly in patients with severe forms of COVID-19 [ 72 , 73 ].…”
Section: Extrapulmonary Manifestations and The Role Of Gut Microbiota...mentioning
confidence: 99%
“…Zwischen 30 und 40 % der kritisch erkrankten COVID-19 Patient*innen entwickeln eine akute Nierenschädigung (AKI) [ 24 , 25 ]. Als zugrundeliegende Mechanismen werden neben der COVID-19 assoziierten systemischen Inflammationsreaktion, direkte Endothelschädigungen der Niere angenommen.…”
Section: Nierenersatztherapieunclassified